2021
DOI: 10.1017/s1368980021004602
|View full text |Cite
|
Sign up to set email alerts
|

Associations between farmers’ market shopping behaviours and objectively measured and self-reported fruit and vegetable intake in a diverse sample of farmers’ market shoppers: a cross-sectional study in New York City and rural North Carolina

Abstract: Objective: To examine cross-sectional associations between farmers’ market shopping behaviors and objectively measured and self-reported fruit and vegetable (FV) intake among rural North Carolina (NC) and New York City (NYC) shoppers. Design: Cross-sectional intercept surveys were used to assess self-reported FV intake and three measures of farmers’ market shopping behavior: (1) frequency of purchasing FV, (2) variety of FV purchased, and (3) dollars spent on FV. Skin carotenoids, a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Prior studies provide consistent evidence that shopping at a FM at least once in the past year was associated with higher reported fruit [13] or FV intake [14] and greater likelihood of consuming five or more FV daily [15]. Furthermore, more frequent FM shopping was associated with more frequent FV consumption [16] as well as higher reported [17][18][19] and objectively measured [19] FV intake.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Prior studies provide consistent evidence that shopping at a FM at least once in the past year was associated with higher reported fruit [13] or FV intake [14] and greater likelihood of consuming five or more FV daily [15]. Furthermore, more frequent FM shopping was associated with more frequent FV consumption [16] as well as higher reported [17][18][19] and objectively measured [19] FV intake.…”
Section: Introductionmentioning
confidence: 74%
“…We also found that FM shoppers typically shopped for FV at a FM two or three times a month and spent approximately USD 23 in money or benefits at each time. Prior research suggests that FM shopping and frequency of FM shopping is positively associated with self-reported and objectively assessed FV intake [13][14][15][16][17][18][19]. Regular FM shopping may be a habit that supports FV intake, which is an important aspect of healthy eating.…”
Section: Discussionmentioning
confidence: 99%
“…Both geographic and financial access to farmers' markets are important for participants to procure and consume fresh FV. Shopping at farmers' markets is associated with greater FV intake [25,26] and is an established strategy to promote FV intake. Future research should examine strategies that alleviate both financial and geographic barriers to accessing farmers' markets through produce prescription programs.…”
Section: Discussionmentioning
confidence: 99%
“…Shopping at farmers markets has been positively associated with fruit and vegetable intake [ 14 ], but cost is a barrier for those experiencing food insecurity [ 15 ]. Virginia Fresh Match (VFM) is a Food Insecurity Nutrition Incentive (FINI) Program—a funded, statewide network of farmers markets and food retail outlets that provides nutrition incentives for fruits and vegetables at the point of purchase to SNAP customers.…”
Section: Introductionmentioning
confidence: 99%